2010
DOI: 10.1093/eurheartj/ehq331
|View full text |Cite
|
Sign up to set email alerts
|

A propensity score-adjusted retrospective comparison of early and mid-term results of mitral valve repair versus replacement in octogenarians

Abstract: Elective mitral repair can be performed with low operative mortality and good long-term outcomes in selected octogenarians with degenerative mitral disease, and is associated with better long-term survival than mitral replacement. The survival benefit associated with surgery for non-degenerative disease is more questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 23 publications
9
110
2
1
Order By: Relevance
“…However, they included patients with endocarditis (1.8% in MV‐repair and 13.7% in MVR) and had a higher rate of patients with ischemic MV disease (32.2% in MV‐repair) as compared to our cohort. The mean age of the study population was 83 years, which is higher than in our cohort and may also explain the difference in outcomes 12. Vassileva and colleagues showed a lower operative mortality in elderly patients of 3.9% for MV‐repair and 8.9% for MVR, but they reported only on outcomes of isolated MV procedures 8.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, they included patients with endocarditis (1.8% in MV‐repair and 13.7% in MVR) and had a higher rate of patients with ischemic MV disease (32.2% in MV‐repair) as compared to our cohort. The mean age of the study population was 83 years, which is higher than in our cohort and may also explain the difference in outcomes 12. Vassileva and colleagues showed a lower operative mortality in elderly patients of 3.9% for MV‐repair and 8.9% for MVR, but they reported only on outcomes of isolated MV procedures 8.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, the benefit of improved long‐term survival after MV‐repair is often believed not to apply in patients whose remaining life expectancy is naturally limited to less than 10 years. Published data on long‐term outcomes in elderly patients are contradictory, and the cohorts of MV‐repair and MVR in these reports often were not comparable 7, 10, 11, 12. While European and American guidelines in general favor MV‐repair over MVR, if a durable repair can be achieved, European guidelines do not address the elderly population with MV disease,13 and American guidelines recommend MV‐repair in patients >65 years only in the presence of symptomatic primary MV disease 14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 48 articles were selected for full-text reading, of which 41 reports that failed to meet the eligibility criteria were eliminated. Consequently, seven observational studies (11)(12)(13)(14)(15)(16)(17) that were published from 2004 to 2016 were included in our meta-analysis.…”
Section: Study Searchmentioning
confidence: 99%
“…The proportion of octogenarian patients with postoperative stroke following mitral valve repair was reported as 5.3% and 3.1% by Nloga, et al 21) and Chikwe, et al, respectively. 23) In our study, 2 patients showed intraoperative stroke, which may be related to aortic manipulation. Because elderly patients often have a diseased aorta, the cannulation site must be carefully selected.…”
Section: Discussionmentioning
confidence: 51%